Do Americans Favor Female or Male Politicians? Evidence from Experimental Elections - Panu Poutvaara; Andreas Graefe (CESifo GmbH, 2024)
Women are severely underrepresented in American politics, especially among Republicans. This underrepresentation may result from women being less willing to run for office, from voter bias against women, or from political structures that make it more difficult for women to compete. Here we show how support for female candidates varies by voters' party affiliation and gender. We conducted experimental elections in which participants made their vote choices based solely on politicians' faces. When choosing between female and male candidates, Democrats, and especially Democratic women, preferred female candidates, while Republicans were equally likely to choose female and male candidates. These patterns held after controlling for respondents' education, age, and political knowledge, and for candidates' age, attractiveness, and perceived conservatism. Our findings suggest that voter bias against women cannot explain women's underrepresentation. On the contrary, American voters appear ready to further narrow the gender gap in politics.
Keywords: D72; J16; H23; 330; gender; elections; gender discrimination; political candidates; redistribution